Phylogeny of Celastraceae subfamily Hippocrateoideae inferred from morphological characters and nuclear and plastid loci - Coughenour, Jennifer M.; Simmons, Mark P.; Lombardi, Julio A. [UNESP]; Yakobson, Kendra; Archer, Robert H. (Academic Press Inc. Elsevier B.V., 2011)
The phylogeny of Celastraceae subfamily Hippocrateoideae (similar to 100 species and 19 genera in the Old and New World tropics) was inferred using morphological characters together with plastid (matK, trnL-F) and nuclear (ITS and 26S rDNA) genes. The subfamily is easily recognized by the synapomorphies of transversely flattened, deeply lobed capsules and seeds with membranous basal wings or narrow stipes together with bisexual, 5-merous flowers that generally have an extrastaminal disk and three stamens. Hippocrateoideae, like Salacioideae, are inferred to have an Old World origin. The narrow stipes of Neotropical species that are water-dispersed are inferred to be derived within the subfamily from ancestral species with wind-dispersed winged seeds. Helictonema, a monotypic genus endemic to tropical Africa, has a small, white, spongy aril that is located at the base of the seed wing and appears to be unique within Hippocrateoideae. Our inference that Helictonema is sister to the remaining members of the subfamily, considered in the context of Sarawakodendron being sister to Salacioideae, suggests that small arils and capsular fruit were primitive within both subfamilies. The aril became dramatically enlarged within Salacioideae, in which the fruits are berries, and lost entirely within Hippocrateoideae, in which the fruits are transversely flattened capsules. All five Old World taxa of Prionostemma and all eight currently recognized species within Simirestis are transferred to Pristimera, one South African variety of Pristimera is raised to species level, and all three taxa in Pristimera subgenus Trochantha are transferred to the new genus Trochantha. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Aril homology; Celastraceae; Helictonema; Hippocrateoideae; Seed dispersal; Trochantha